Analisis Faktor-Faktor Dominan Tentang Kepuasan Konsumen Dalam Pembelian Rumah Pada Proyek Perumahan Persada Mas Banjarmasin - Elva Shanty Widuri (Media Ilmiah Teknik Sipil, 2020)
To find out the dominant factors about consumer satisfaction in buying a house in a housing project, there must be involvement between the developer and the consumer. This is intended to find out the priorities and expectations of consumers in buying a house in the housing project. The importance of knowing consumer satisfaction is to make strategies in an effort to improve and improve the quality of housing products. Customer satisfaction really depends on the facility, what are the dominant factors about consumer satisfaction in buying a house in a housing project. The dominant factors that consumers want in buying a house are obtained from information on consumers who live in the area. This information is obtained through distributing questionnaires which are then processed by validity analysis, reliability analysis, factor analysis, and cross-tabulation analysis. By getting the dominant factors about consumer satisfaction in buying a house in a housing project, the development party can improve and improve existing facilities so that consumers feel satisfied so that they become a source of sustainable competitiveness